ALEKTOROPHOBIA AMONG FIRST YEAR DENTAL STUDENTS IN CHENNAI - A QUESTIONNAIRE SURVEY - Snigdha Bharadwaz, Dhanraj M. Ganapathy, L. Keerthi Sasanka, (Drugs and Cell Therapies in Hematology, 2021)
Background: Phobia is a type of disorder which is characterised by fear or anxiety. Alektorophobia is referred to as the fear of chicken or hens. It is a type of specific phobia which can be mostly observed in children and adolescents, especially females. Alektorophobia is a rare phobia. Aim: The aim of the study was to evaluate Alektorophobia among first year dental students in Chennai. Materials and Methods: A survey was conducted which was cross sectional. A self-administered questionnaire was distributed among the first year dental students using an online platform google forms and 100 students participated in the survey. Data was collected and analysed by using SPSS software. Pearson Chi square was done to correlate the gender and phobia of the participants. Results: 63% of the participants had a fear or phobia. 30% of them knew about alektorophobia. 5% of the population showed symptoms of alektorophobia. While comparing both the genders, female students exhibited higher levels of awareness and anxiety about phobia than the male students. Conclusion: Phobia is experienced by the majority of the people. Alektorophobia is still an uncommon phobia not only among the first year dental students but the whole population in general. It is best to overcome it at the early stages.